Tujuan Pendidikan Islam dalam Pandangan Nurcholish Madjid - Safitri, Lis; Manshur, Fadlil Munawwar (Tsamratul Fikri | Jurnal Studi Islam, 2016)
This article is a qualitative research explained by descriptive-inferential method and analyzed by method of hermeneutics of Hans George Gadamer. Nurcholish Madjid (1939-2005) had more thorough idea about the objective of Islamic education. The ultimate goal of human life is ‘abd and khalîfah. God gives emotions and fit}rah to achieve it. Emotion, lead by knowledge, will bring human to the goodness or badness. ‘Abd and khalîfah has manifested in good worshiping and good in social life.